Quality Management of Private Islamic University Education: A Study on Universitas Islam Syekh-Yusuf Tangerang-Indonesia - Nur, Muhammad (JURNAL ILMIAH ILMU ADMINISTRASI, 2024)
Total Quality Management  is a comprehensive approach to quality improvement that involves all members of an organization. In the context of education, TQM aims to enhance the quality of educational services by focusing on customer satisfaction, continuous improvement, and employee involvement. This study examines the quality management of private Islamic university education: a study on Universitas Islam Syekh-Yusuf Tangerang Indonesia. The quality of management in Islamic university education is a significant area that leadership should recognize. This study is qualitative, using data from interviews, observations, and documentation. The results of this study relate to: (1) focus on customers; (2) leadership; (3) people involvement; (4) systems approach to management; (5) continuous improvement; (6) factual approach in decision making; and (7) mutually beneficial supplier relationships. This research demonstrates that the effective implementation of Total Quality Management (TQM) principles can enhance customer satisfaction and organizational performance.